CRITERIAS FOR CREATING SPEAKING ACTIVITIES OF LANGUAGE LEARNERS - Feruza Komiljaniovna Kurbanova; Abdunazarova Adiba Abdushukur qizi; Nurimboyeva Go`zal Vaxob qizi (Journals Park Publishing, 2023)
In this article we aim to discuss some relevant ideas for having effective and helpful activities to reach higher speaking level. Firstly, we should know the purpose of speaking activity what we want to focus on, fluency or accuracy? We need to keep these questions in mind when preparing a speaking task.
Keywords: monitor, participants, interlocutor